MARAH DAN KUALITAS HIDUP ORANG YANG MENGALAMI PSIKOSOMATIK - Gamayanti, Witrin; Hidayat, Ila Nurlaila (Faculty of Psychology, Diponegoro University, 2019)
This study aims to determine the correlation of anger to the quality of life of people who experience psychosomatic. negative emotions may cause psychosomatic disorders, including anger. These emotions affect the neurological working mechanism that activates an excessive number of neural, neuroendocrine and endocrine and attack the individuals weakest organs. By using non-probability sampling of purposive sampling type, the research was conducted on 106 college student of UIN Sunan Gunung Djati Bandung who experienced the psychosomatic disorder, based on the screening result of inventory to detect the psychosomatic disorder. The data were obtained through two scales : State-trait Anger Expression Inventory-2 (STAXI-2) (51 items; Î±= .819), and the quality of life scale of WHO that has been adapted (52 items; Î±= .863). The data were analyzed with simple linear regression test. The results show that anger has a significant correlation to the quality of life of people who experience psychosomatic, F(1, 104) = 6.063; p = .015. As the anger getting higher, quality of life on an individual who experiences psychosomatic would be getting lower, Î² = -.235; p = .015.